2014
DOI: 10.1038/hdy.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale patterns in snowmelt timing affect gene flow and the distribution of genetic diversity in the alpine dwarf shrub Salix herbacea

Abstract: Current threats to biodiversity, such as climate change, are thought to alter the within-species genetic diversity among microhabitats in highly heterogeneous alpine environments. Assessing the spatial organization and dynamics of genetic diversity within species can help to predict the responses of organisms to environmental change. In this study, we evaluated whether small-scale heterogeneity in snowmelt timing restricts gene flow between microhabitats in the common long-lived dwarf shrub Salix herbacea L. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 68 publications
(102 reference statements)
5
53
0
Order By: Relevance
“…allelic richness: 8.93 ± 0.27 and 6.81 ± 0.29 for snowbeds and ridges, respectively), and gene low, measured as the number of migrants per generation, was asymmetric toward the snowbeds (Figure 3). Overall, these results are consistent with snowbeds acting as sinks of genetic diversity and seed dispersal preventing snowmelt-driven genetic isolation [22].…”
Section: Asymmetry In Seed Dispersalsupporting
confidence: 77%
See 3 more Smart Citations
“…allelic richness: 8.93 ± 0.27 and 6.81 ± 0.29 for snowbeds and ridges, respectively), and gene low, measured as the number of migrants per generation, was asymmetric toward the snowbeds (Figure 3). Overall, these results are consistent with snowbeds acting as sinks of genetic diversity and seed dispersal preventing snowmelt-driven genetic isolation [22].…”
Section: Asymmetry In Seed Dispersalsupporting
confidence: 77%
“…Lack of population structure was supported by a STRUCTURE analysis. This absence of population diferentiation, even in microhabitats with highly diferent snowmelt dates, may be mediated by high and asymmetric seed dispersal [22].…”
Section: Asymmetry In Seed Dispersalmentioning
confidence: 99%
See 2 more Smart Citations
“…In a genetic study along the same transects, Cortés et al (2014) found high gene-flow in S. herbacea populations among altitudes and microhabitats. High levels of gene flow between our study populations may have counteracted local adaptation to soil microbes (Sambatti & Rice, 2006).…”
Section: Lack Of Home-soil Advantage Within the Current Rangementioning
confidence: 99%